American critics and criticism - Long, Sue (My University, 1896)
Introduction: With the “Revival of Learning” there came into life a new form of literary activity. It was born of man’s timeless into the realms of an unknown literature, it was developed by his learning more and more the fact that books are not the reflections of real life, and finally that it was destined to become a most powerful factor in the sphere of its origin. The earliest type of criticism has been most fitly described as “textual” for it dealt with phrases and texts alone. It was a purely scientific conception. As an outgrowth of this we find in time that criticism has made another evolution, losing somewhat its scholarly aspect and taking into consideration the laws of art and beauty.
Citation: Long, Sue. American critics and criticism. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: American; Critics; Literature; English; Theses; Manuscripts (documents)